The impact of shariah-compliance extensiveness screening on the initial performance of Malaysian IPOs - Che Embi, Nor Azizan; Rahim, Ruzita; Ibrahim, Izani (2013)
This study suspects that relying on the current Shariah screening process on financial aspects by Shariah Advisory Council of Malaysia may be not sufficient as the two important ratios which are Debt ratio and ARTA ratio highlighted by Council of Islamic Fiqh Academy (CIFA) are not being used. The study observed 347 Shariah-compliant companies and 37 non-compliant Shariah companies that issued IPOs from January 1999 until December 2008. Obviously, when the Shariah IPOs samples are ranked based on the level of extensiveness, the difference in the initial returns between the most extensive Shariah IPOs and non-Shariah compliant IPOs prevails.